2015
DOI: 10.1186/s12959-015-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Stent thrombosis caused by metal allergy complicated by protein S deficiency and heparin-induced thrombocytopenia: a case report and review of the literature

Abstract: A 43-year-old woman recipient of a bare metal coronary stent during an acute anterior myocardial infarction was repeatedly hospitalized with recurrent stent thrombosis (ST) over the following 3 years. Emergent coronary angiography showed a thrombus in the in-stent segment of the proximal left anterior descending artery. We repeatedly aspirated the thrombus, which immediately reformed multiple times. The discontinuation of heparin and administration of thrombolytics and argatroban, followed by repeated balloon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Total occlusion was mentioned by D’Arrigo et al in femoral artery stenting. 49 Konishi et al 50 reported thrombus formation and concurrent in-stent stenosis of Driver TM nickel- stent which led to ST-elevation myocardial infarction. Eosinophilic infiltra extracted from a thrombus was also demonstrated in post-mortem individuals who exhibited ST changes following endograft hypersensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total occlusion was mentioned by D’Arrigo et al in femoral artery stenting. 49 Konishi et al 50 reported thrombus formation and concurrent in-stent stenosis of Driver TM nickel- stent which led to ST-elevation myocardial infarction. Eosinophilic infiltra extracted from a thrombus was also demonstrated in post-mortem individuals who exhibited ST changes following endograft hypersensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, oral antihistamines were used in 5 patients in conjunction with steroid therapy. 17 , 18 , 23 , 45 , 50 In 3 patients, anti-platelet medications were administered, with 2 patients administered clopidogrel following an adverse reaction for the treatment of congenital heart diseases. 34 , 35 Following the severity of the hypersensitivity reaction, Guerra et al described one patient who was administered immunosuppressive therapy in the form of mycophenolic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[68][69][70] Konishi et al reported a case with recurrent stent thrombosis in a patient with proved stent allergy who can benefit of systemic corticotherapy. 71 Besides antiplatelet therapy, low doses of steroids might confer clinical benefits and lower the incidence of stent thrombosis due to their anti-inflammatory properties.…”
Section: Stent Thrombosis/kounis Syndromementioning
confidence: 99%
“…The first generation of cardiovascular materials primarily consisted of stainless steel, titanium alloys, and cobalt chromium alloys . Although these metal alloys contain desirable properties, such as stiffness, strength, corrosive resistance, and haemocompatibility, direct contact with blood for a prolonged time interval can cause thrombosis . Therefore, over time metal alloys have been slowly replaced by synthetic polymers, including polyesters, polyurethanes, polyamides, and polytetrafluoroethylenes.…”
Section: Biomaterials Strategiesmentioning
confidence: 99%